Cirugía de rinoplastia con injerto de punta nasal de silicona tallada realizada en una clínica de Lima, Perú en el 2022 - Chau Ramos, Enrique Antonio (2024)
Objective: To demonstrate the stability of the nasal tip over time with the use of carved silicone among patients with nasal tip stability deficit, previous aesthetic rhinoplasty and manipulation of the nasal septum. Materials and methods: A descriptive, analytical, interventional study using the nasal tip stabilization reconstruction technique performed at a private clinic in the city of Lima, Peru, in 2022. The study included 22 cases of patients between the ages of 30 and 55 with tip instability, previous rhinoplasty and manipulated nasal septum, without comorbidities. The patients were evaluated in the first, third and sixth months and one year after the reconstruction and stabilization of the nasal tip. Non-probabilistic sampling was performed. No sample was used, since the total number of patients who met the inclusion criteria were included. All the participants underwent the surgical technique with carved silicone. Results: With the surgical technique using carved silicone, less bleeding and less bruising were observed. In the follow-up one year after surgery, the technique maintained similar characteristics over time, in both alignment and height of the nasal tip. One case of extrusion of the silicone sheet was evidenced as a complication following trauma caused by a patient's fall. Conclusions: Silicone is widely accepted as a material employed for facial contouring with extended use in rhinoplasty. Our study demonstrated that it provides long-lasting support for the nasal tip. It is a viable alternative in rhinoplasties that do not have autologous cartilage or where the use of costal cartilage is sought. Silicon, being a readily available synthetic material that is easily moldable and does not reabsorb, is a useful alternative that shortens operating time and maintains tip projection.